2014
DOI: 10.7314/apjcp.2014.15.18.7553
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Hiwi Promotes Growth of Human Breast Cancer Cells

Abstract: The Piwi subfamily comprises two argonaute (Ago) family proteins, which are defined by the presence of PAZ and Piwi domains, with well known roles in RNA silencing. Hiwi, a human Piwi subfamily member, has been shown to play essential roles in stem cell self-renewal and gametogenesis. Recently, accumulating reports have indicated that abnormal hiwi expression is associated with poorer prognosis of multiple types of human cancers, including examples in the breast. However, little is known about details of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…To further investigate the functional potential of these piRNAs, we assessed these piRNAs in the context of PIWI proteins. Using mRNA expression data for 253 patients from The Cancer Genome Atlas, we identified PIWIL1 to be significantly upregulated in current smoker vs. lifelong nonsmoker samples, in accordance with previous studies identifying overexpression of this gene in other carcinomas ( p < 0.05, FDR < 0.05) [3336]. Correlations of our 13-member piRNA panel to PIWIL1 indicated that NONHSAT081250 , a piRNA downregulated in smoking-associated HNSCCs, exhibited significantly reduced expression with upregulation of PIWIL1 , suggesting a potential mechanistic interaction between these elements ( p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…To further investigate the functional potential of these piRNAs, we assessed these piRNAs in the context of PIWI proteins. Using mRNA expression data for 253 patients from The Cancer Genome Atlas, we identified PIWIL1 to be significantly upregulated in current smoker vs. lifelong nonsmoker samples, in accordance with previous studies identifying overexpression of this gene in other carcinomas ( p < 0.05, FDR < 0.05) [3336]. Correlations of our 13-member piRNA panel to PIWIL1 indicated that NONHSAT081250 , a piRNA downregulated in smoking-associated HNSCCs, exhibited significantly reduced expression with upregulation of PIWIL1 , suggesting a potential mechanistic interaction between these elements ( p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…The involvement of PIWI proteins in cancer was first reported in seminomas in which PIWILI might participate in enhancing the proliferation of germ cells but not somatic cells [33]. Very recently, the hiwi gene was also reported to promote the growth of human breast tumors [46], gastric tumors [40], and hepatocellular carcinoma cells [72]. The piwil2 gene was suggested to modulate the proliferation of colon cancer [58] and breast cancer [51,53].…”
Section: Piwis Are Involved In Promoting Cell Proliferationmentioning
confidence: 99%
“…PIWIL1 (Piwi‐like RNA‐mediated gene silencing 1), also known as HIWI, contains two conserved domains: the PAZ domain in middle and the PIWI domain in C‐terminal . Current discoveries have shown that PIWIL1 is involved in tumorigenesis in various cancers, including proliferation, migration and invasion of cancers . Meanwhile, evidences have demonstrated that the dysfunction of circadian rhythms is associated with tumours .…”
Section: Introductionmentioning
confidence: 99%